What Can Charcoal Reflectance Tell Us About Energy Release in Wildfires and the Properties of Pyrogenic Carbon? - Belcher, Claire M.; New, Stacey L.; Santín, Cristina; Doerr, Stefan H.; Dewhirst, Rebecca A.; Grosvenor, Mark J.; Hudspith, Victoria A. (Frontiers in Earth Science, 2018)
Here, we explore how charcoal formation under different heating regimes and circumstances leads to chars of different physical properties. In order to do this, we have undertaken (1) carefully controlled laboratory experiments that replicate the different heating regimes that might be experienced during a wildfire and (2) two experimental wildfires where heat variations were monitored across the burn from which resulting charcoal has been studied. The charcoal properties were assessed using charcoal reflectance that measures the light reflected back from the charcoals structure and which links to changes in its structural properties. We find that increased total heat released during combustion positively correlates with increased charcoal reflectance and that this is evidenced from both our laboratory experiments and experimental wildfires. Charcoals that related to lower total heat release were found to have more lignin remaining than those subjected to greater heating indicating that charcoals formed in lower energy regimes are likely to be more susceptible to post-fire degradation. We conclude that charcoal reflectance may make a useful metric with which to determine the distribution of energy delivery across a burned area and that this may be utilized to inform both variations in fire severity and enable the prediction of long-term C budgeting for different types of wildfire.